Determination of the mechanical properties of recycled brick aggregate concrete by multivariate regression analysis (Advances in Civil and Architectural Engineering, 2024)
This study presents regression models for prediction of compressive strength and modulus of elasticity, applying variables such as the percentage of recycled brick aggregate replacement, cement content, and water-cement ratio. A comprehensive database was constructed, comprising data from 180 experimental tests conducted on recycled brick aggregate concrete. The database includes the findings of compressive strength and modulus of elasticity testing. Multivariate statistical analysis was performed on the data and prediction models were created. During the review of the existing literature, a research gap was observed, where the modulus of elasticity was always expressed with dependence on compressive strength. The modulus of elasticity and compressive strength are modelled separately using the values of the contents of the concrete mixture. From the derived equations, the relationship that the modulus of elasticity is the second root of the compressive strength is recognized, which is in accordance with the functional relationships of the modulus of elasticity and compressive strength determined by previous authors. These models were then evaluated and confirmed using a subset of 20 samples for compressive strength and 13 samples for modulus of elasticity, which were excluded from the main database. The main results confirmed the applicability of the proposed equations with acceptable accuracy for initial concrete mixtures and thus, can be used as guidelines by future researchers.